KONSEP KESAKRALAN MIRCEA ELIADE DALAM TRADISI PERINGATAN MALAM SATU SURO DI KOTAGEDE YOGYAKARTA - Yuwono, Adhimas Alifian; Nurhuda, Abid; Ansori, Inamul Hasan (Dharmasmrti: Jurnal Ilmu Agama dan Kebudayaan, 2024)
This article aims to show the representation of Mircea Eliade's concept of "sacred" in the tradition of commemorating the first night of Suro in Kotagede, Yogyakarta. This type of research is qualitative with a literature study approach. Data collection was carried out by collecting literary sources in the form of books and journals related to formal objects, namely the thoughts of Mircea Eliade, and material objects, namely the tradition of commemorating the first night of Suro in Kotagede, Yogyakarta. The results of this research are that this tradition occurred because of the hierophony, namely between the month of Suro which is believed to bring both blessings and dangers and the place of implementation, namely the tombs of the Mataram kings. The myth that emerged was in the form of a belief in getting blessings and being protected from danger. Sacred symbols are manifested in the reading of tahlil, eating jenang suran, and burning incense. Meanwhile, the concept of the cosmos occurs at the time the tradition is carried out, because when the tradition takes place, there is a sacred time and a sacred place at the same time.